Chatbot as a Persuasive Technology to Promote Responsible Recycling in the City of Lima - Flores, Kevin Anderson Franco (2022)
Persuasive technologies have gained popularity around the world. This type of technology aims to change the behavior of people in different circumstances using the persuasion method. Within this classification of technologies we have virtual assistants whose function is to interact in a personalized way with the user. This research aims to provide a solution to the low levels of recycling habits in citizens, which is caused by inefficient programs and/or activities applied by authorities, educational centers and households of socioeconomic levels. low fees by promoting recycling issues. We proposed the use of a virtual assistant to increase knowledge and show the benefits of recycling, in order to generate an improvement in the behavior of the population. To validate this research, two knowledge tests on recycling issues were administered to 69 university students at the beginning and end of the process. After using our virtual assistant, the participants appeared and increased their knowledge by 70.49%.